The Effects of Bilirubin and Lumirubin on Metabolic and Oxidative Stress Markers - Dvořák, Aleš; Pospíšilová, Kateřina; Žížalová, Kateřina; Capková, Nikola; Muchová, Lucie; Vecka, Marek; Vrzáčková, Nikola; Křížová, Jana; Zelenka, Jaroslav; Vítek, Libor (Frontiers in Pharmacology, 2021)
For severe unconjugated hyperbilirubinemia the gold standard treatment is phototherapy with blue-green light, producing more polar photo-oxidation products, believed to be non-toxic. The aim of the present study was to compare the effects of bilirubin (BR) and lumirubin (LR), the major BR photo-oxidation product, on metabolic and oxidative stress markers. The biological activities of these pigments were investigated on several human and murine cell lines, with the focus on mitochondrial respiration, substrate metabolism, reactive oxygen species production, and the overall effects on cell viability. Compared to BR, LR was found to be much less toxic, while still maintaining a similar antioxidant capacity in the serum as well as suppressing activity leading to mitochondrial superoxide production. Nevertheless, due to its lower lipophilicity, LR was less efficient in preventing lipoperoxidation. The cytotoxicity of BR was affected by the cellular glycolytic reserve, most compromised in human hepatoblastoma HepG2 cells. The observed effects were correlated with changes in the production of tricarboxylic acid cycle metabolites. Both BR and LR modulated expression of PPARa downstream effectors involved in lipid and glucose metabolism. Proinflammatory effects of BR, evidenced by increased expression of TNFa upon exposure to bacterial lipopolysaccharide, were observed in murine macrophage-like RAW 264.7 cells. Collectively, these data point to the biological effects of BR and its photo-oxidation products, which might have clinical relevance in phototherapy-treated hyperbilirubinemic neonates and adult patients.